Entomofauna aquática do Ribeirão das Anhumas (Bacia hidrográfica do Rio Mogi-Guaçú, SP) : influência do represamento e do uso da terra na estrutura da comunidade - Saulino, Hugo Henrique Lanzi (Universidade Federal de São Carlos, 2012)
Changes in river basins such as the deforestation of riparian vegetation, the expansion of agricultural activities and construction of dams, are examples of anthropogenic interference, which interferes with the diversity of aquatic insects in streams and rivers. This study aimed to investigate the distribution patterns of communities of aquatic insects in a longitudinal profile of the Ribeirão Anhumas, discontinued by the construction of five impoundments and the influence of different land uses. Sampling occurred in the river basin of the Ribeirão Anhumas in an area upstream and downstream of the five dams, on the towards headstream/mouth of the creek. We analyzed the concentration of potentially bioavailable metals (Fe, Mg, Mn, Cu, Zn, Ni, Cd and Cr) in sediment. For the sampling effort fauna, the quick sampler method was used for a period of two minutes. Specimens were identified to lowest possible taxonomic level and classified by feeding groups. The highest concentrations of metals in the sediment were recorded in parts of the dam 4 (R4), which is observed around sugar cane farming, the analysis indicated contamination by Ni. 2498 aquatic insects were identified, wich distributed in 92 genera. Polypedilum (Chironomidae, Diptera) was the taxon more representative of the community, as well as the guilds of the predators and gathering-colectors. The stretches with preserved riparian vegetation had the highest values of richness, taxonomic diversity and water quality score. The Student statistical test indicated that there were no significant differences in the abundance and richness between the streches. Diversity indices showed a decrease in diversity between the upstream and downstream sections, and longitudinal profile. We concluded that the basin of the Ribeirão Anhumas is well preserved, where there was no interference from lotic habitat discontinuity of the dams, as well as different land uses low-impact exercise on aquatic insect community.
Keywords: Ecologia aquática; Represas; Rios e riachos; Insetos aquáticos; Heterogeneidade; Substrato; EPTC; Heterogeneity; Substratum; EPTC; Dams; CIENCIAS BIOLOGICAS::ECOLOGIA